2023
DOI: 10.1108/jmh-07-2023-0069
|View full text |Cite
|
Sign up to set email alerts
|

Employee based brand equity: a systematic review of literature, framework development, and implications for future research

Bianca Sousa,
Pedro Ferreira

Abstract: Purpose Through a systematic literature review, this paper aims to endeavor to present a thorough historical perspective on the evolution of employee-based brand equity (EBBE), offering a comprehensive understanding of its development. The study explores the general model, causes and effects of EBBE, as well as the role of culture, leadership and brand management in building EBBE. The paper proposes an integrative framework to understand the interrelationships between the various dimensions of EBBE and offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The need to develop scientific reviews on this topic has been identified in several studies [11][12][13][14]. However, researchers have focused on brand equity themes without Sustainability 2024, 16, 5412 2 of 19 considering a broader range of sources, and some authors have recommended further investigation of brand equity in social media [11].…”
Section: Introductionmentioning
confidence: 99%
“…The need to develop scientific reviews on this topic has been identified in several studies [11][12][13][14]. However, researchers have focused on brand equity themes without Sustainability 2024, 16, 5412 2 of 19 considering a broader range of sources, and some authors have recommended further investigation of brand equity in social media [11].…”
Section: Introductionmentioning
confidence: 99%